ответ: -3
Пошаговое объяснение:
Сначала раскрываем квадрат разности и берём производную
f(x) = (x-6)^2 (x+3) - 3 = (x^2-12x+36)(x+3) - 3
f'(x) = (x-6)2+(x+3)·(2·x-12)
Находим нули производной:
(x-6)2+(x+3)·(2·x-12) = 0
2(x^2 -2x - 24) = 0
x1 = -4; x2=6;
На числовой прямой находит x min = 6
y наим = (6-6)^2 * (6+3) - 3 = -3
ответ: -3
Пошаговое объяснение:
Сначала раскрываем квадрат разности и берём производную
f(x) = (x-6)^2 (x+3) - 3 = (x^2-12x+36)(x+3) - 3
f'(x) = (x-6)2+(x+3)·(2·x-12)
Находим нули производной:
(x-6)2+(x+3)·(2·x-12) = 0
2(x^2 -2x - 24) = 0
x1 = -4; x2=6;
На числовой прямой находит x min = 6
y наим = (6-6)^2 * (6+3) - 3 = -3